2004
DOI: 10.1086/423790
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of the R620W Polymorphism of Protein Tyrosine Phosphatase PTPN22 with Human SLE

Abstract: We genotyped 525 independent North American white individuals with systemic lupus erythematosus (SLE) for the PTPN22 R620W polymorphism and compared the results with data generated from 1,961 white control individuals. The R620W SNP was associated with SLE (genotypic P=.00009), with estimated minor (T) allele frequencies of 12.67% in SLE cases and 8.64% in controls. A single copy of the T allele (W620) increases risk of SLE (odds ratio [OR]=1.37; 95% confidence interval [CI] 1.07-1.75), and two copies of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
411
7
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 596 publications
(446 citation statements)
references
References 16 publications
23
411
7
5
Order By: Relevance
“…Several studies have associated the 1858T allele with autoimmune diseases [18][19][20][21][22][23][24][25] and generalised vitiligo is thought to have an autoimmune aetiology, 1 although this remains undefined. The frequent association of vitiligo with autoimmune disorders and the demonstration of autoantibodies to melanosomal proteins in the serum of patients with the disease support this theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have associated the 1858T allele with autoimmune diseases [18][19][20][21][22][23][24][25] and generalised vitiligo is thought to have an autoimmune aetiology, 1 although this remains undefined. The frequent association of vitiligo with autoimmune disorders and the demonstration of autoantibodies to melanosomal proteins in the serum of patients with the disease support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Recently, the missense R620W polymorphism in the PTPN22 gene at nucleotide 1858 (1858C-T) in codon 620 (620Arg-Trp) has been associated with autoimmune diseases including type I diabetes mellitus, Graves' disease, systemic lupus erythematosus and rheumatoid arthritis. [18][19][20][21][22][23][24][25] The gene, located on chromosome 1p13, 19 encodes lymphoid protein tyrosine phosphatase (LYP), which is important in the negative control of T lymphocyte activation. 26 Lymphoid protein tyrosine phosphatase is expressed in T lymphocytes and associates with C-terminal Src kinase (CSK) to form a complex that suppresses the T-cell receptor signalling kinases LCK and FYN.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that B‐cells from carriers of this PTPN22 risk allele contained high frequencies of autoreactive clones compared with those from non‐carriers showing how a single polymorphism at one genetic locus can affect the B‐cell repertoire 61. This PTPN22 polymorphism is a gain‐of‐function variant leading to reduced B‐ and T‐cell receptor signalling,62, 63 and has been associated with a range of autoimmune diseases, including RA,64, 65 type 1 diabetes66 and SLE 67. Similar studies on variation in other genes are likely to provide further useful information on how specific biological pathways regulate the B‐cell repertoire.…”
Section: Slementioning
confidence: 99%
“…13,14 This finding has been extensively replicated, [15][16][17] and is now accepted as the most robust genetic association with RA outside of the MHC. 18 Interestingly, the 620W PTPN22 allele is also associated with several other autoimmune disorders including type 1 diabetes, 19,20 autoimmune thyroid disease, 21 systemic lupus erythematosus 22,23 and some forms of juvenile arthritis. 24,25 A recent report indicates that additional variability in the PTPN22 locus may account for a more minor proportion of risk for RA.…”
Section: Introductionmentioning
confidence: 99%